Acute effects of small changes in antero-posterior shoe-cleat position on physiological and biomechanical variables in road cycling - Chartogne, M.; Millour, G.; García-López, J.; Duc, S.; Rodríguez-Marroyo, J. A.; Pernía, R.; Bertucci, W. (Sports Biomechanics, 2023)
The aim of this study was to investigate the effect of changes in cycling shoe-cleat position on pedalling biomechanics, physiological variables, and performance in road cycling. Twelve competitive road cyclists performed three pedalling trials with the cleat positioned at the first metatarsal head, 15-mm anterior and 15-mm posterior. Each trial included three sets of 5 min performed at 35%, 50%, and 65% of maximal aerobic power (MAP) followed by a 10-s sprint. Results showed no significant changes in physiological variables, pedalling kinetics, muscular activity of six lower limb muscles, sprint performance and perceived exertion. However, significant differences were found regarding joint kinematics: hip, knee, and ankle angles during both extension and flexion were reduced in the anterior cleat position. Therefore, this study suggests that cleat position does not affect sprint performance, physiological variables, pedalling kinetics, muscle activity, and perceived exertion regardless of the cycling intensity. However, joint kinematics, and particularly knee extension angle which could be related to the risk of overuse injuries, was affected by the shoe-cleat position.